Interactions of ST-elevation myocardial infarction, age, and sex and the risk of major adverse cardiovascular events among Chinese adults: a secondary analysis of a single-centre prospective cohort - Lin Zhou; Wei Yuan; Cuiping Wang; Yi Liang; Peijing Liu (BMJ Open)
Objectives This study aimed to evaluate the interactions of ST-elevation myocardial infarction (STEMI), ageing and sex with respect to the incidence of major adverse cardiovascular events (MACE) among Chinese adults.Design Secondary analysis of a single-centre prospective cohort.Setting Patients who were admitted to cardiology clinics of the Affiliated Hospital of Jiangsu University due to acute myocardial infarction (MI) from June 2017 to November 2019 were eligible for inclusion in the study. This research only examined in-hospital cases.Participants Patients aged <18 years or confirmed dead within 24 hours from admission were excluded. A total of 843 adults were included in the analysis.Primary and secondary outcome measures MACE was defined as any occurrence of cardiovascular mortality, MI recurrence, cardiogenic shock or heart failure. The relative excess risk due to interaction (RERI), attributable proportion (AP) and the synergy index were computed to quantify the interactions. Men without STEMI and adults without STEMI aged <60 years were the reference groups when examining the risk of MACE.Results The female participants with STEMI showed a statistically higher risk of MACE compared with the male participants without STEMI (relative risk (RR): 2.713, CI: 1.350 to 5.426, p=0.005). A 3.327 times higher risk of MACE was detected in the older adults with STEMI (aged ≥60 years) compared with the adults without STEMI aged <60 years (RR: 3.327, CI: 1.414 to 8.955, p=0.01). Older female patients also had an increased risk of MACE (RR: 3.033, CI: 1.432 to 6.777, p=0.005). A positive additive interaction was detected between STEMI and age (RERI: 1.917, CI: 0.196 to 3.637; AP: 0.576, CI: 0.174 to 0.979). STEMI and sex also indicated an additive interaction (AP: 0.459, CI: 0.018 to 0.899).Conclusion In this Chinese population with MI, the risk of MACE was increased by about 2.7 times in women with STEMI compared with men without STEMI. MACE incidence increased by about 3.3 times in older patients with STEMI compared with younger patients without STEMI. STEMI and age, and STEMI and sex, may have a positive additive interaction.